Kualitas Konsumsi Makanan Dengan Kejadian Stunting - Ari, Deni; Hanifah, Iis (Universitas Malahayati Bandar Lampung, 2023)
Background: Stunting is a condition of failure to thrive in children under 5 years of age (toddlers) due to chronic malnutrition and recurrent infections, especially in the first 1000 days of life (HPK), namely from the fetus to the child aged 23 months. The Purpose of this research is to determine the relationship between the quality of food consumption and the incidence of stunting in toddlers aged 6-23 months. Method: This research is a correlation research using a cross sectional approach. The population in this study were mothers and toddlers aged 6-23 months with stunting nutritional status, and a sample of 33 respondents was obtained using simple random sampling. Data collection includes coding, editing and tabulating, then the data is analyzed using SPSS with the chi-square test. To determine the strength and weakness of the relationship, use the Contingency Coefficient Test.Results, it was found that those who consumed poor quality food were 22 toddlers (66.7%). The results of the statistical test obtained Pvalue = 0.027 (probability value (p) <  (0.05) which means that H1 is accepted so it can be concluded that there is a relationship between the quality of food consumption and the incidence of stunting in Glundengan village, Wuluhan sub-district.Conclusion in the contingency coefficient test the value is equal to 0.372 means that the relationship between the quality of food consumption and the incidence of stunting is weak. Suggestion: Mothers who have toddlers with stunted nutritional status are expected to provide quality food intake so that the toddler's nutritional status becomes normal. Keywords: Quality of Food Consumption, Stunting Incidence. ABSTRAK Latar belakang: Stunting adalah kondisi gagal tumbuh pada anak dibawah usia 5 tahun (balita) akibat kekurangan gizi kronis dan infeksi berulang terutama pada periode 1000 hari pertama kehidupah (HPK), yaitu dari janin hingga anak berusia 23 bulan. Tujuan dari penelitian ini adalah untuk mengetahui hubungan kualitas konsumsi makanan dengan kejadian stunting pada balita usia 6-23 bulan.Metode: Penelitian ini merupakan penelitian korelasi menggunakan pendekatan cross sectional. Populasi dalam penelitian ini adalah ibu dan balita usia 6-23 bulan dengan status gizi stunting, dan didapatkaan sampel sebanyak 33 responden yang diambil dengan menggunakan simple random sampling. Pengumpulan data meliputi coding, editing dan tabulating, kemudian data dianalisis menggunakan SPSS dengan chi-square test. Untuk mengetahui kuat lemahnya hubungan menggunakan Uji Koofesiensi kontingensi.Hasil penelitian didapatkan bahwa yang mengkonsumsi makanan yang tidak berkualitas adalah 22 balita (66,7%). Hasil uji statistik didapatkan Pvalue = 0,027 (nilai probabilitas (p)< a (0,05 ) yang artinya H1 diterimaKesimpulan bahwa ada hubungan kualitas konsumsi makanan dengan kejadian stunting di desa glundengan kecamatan wuluhan. Sedangkan pada uji koofesiensi kontingensi dimana nilainya sebesar 0,372 memiliki arti hubungan antara kualitas konsumsi makanan dengan kejadian stunting adalah lemah.Saran: Bagi ibu yang memiliki balita dengan status gizi stunting diharapkan memberikan asupan makanan yang berkualitas agar status gizi balita menjadi normal. Kata Kunci: Kualitas Konsumsi Makanan, Kejadian Stunting.